Analisis Pengaruh Beban, Kepuasan dan Kelelahan Kerja Terhadap Kualitas Pelayanan Dokter dan Perawat di RSU St. Antonius Pontianak - Silaban, Agnes Tiurmaida; Indrawati, Lili; Nurhayati, Nurhayati (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
Hospitals, as healthcare service institutions, play a vital role in providing inpatient, outpatient, and emergency care. Service quality is strongly influenced by the performance of healthcare professionals, particularly doctors and nurses, who face high workloads, job satisfaction demands, and the risk of fatigue. Excessive workload may lead to fatigue, stress, and decreased performance, which in turn affect service quality. On the other hand, job satisfaction and the psychological condition of healthcare workers are also assumed to influence service quality. This study was conducted at RSU St. Antonius Pontianak, a class B referral hospital with a high average daily patient visit rate. The purpose of the study was to analyze the influence of workload, job satisfaction, and work fatigue on the service quality of doctors and nurses. The research employed a quantitative survey design by distributing questionnaires to 100 respondents consisting of doctors and nurses. Data analysis was performed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with the SMARTPLS 3 software. The results indicate that workload has a significant effect on service quality, while job satisfaction and work fatigue have no significant effect on service quality. These findings suggest that workload is the dominant factor determining service quality, whereas job satisfaction and fatigue do not directly reduce service quality because healthcare professionals continue to maintain professionalism and adhere to service standards. This study implies that hospital management should pay greater attention to workload management among healthcare workers through balanced task distribution, proper shift arrangements, and adequate facility support to ensure continuous improvement in service quality.